A case series on post-covid deadly fungal infection: mucormycosis - G., Kalpana; Patil, Amol A.; Shaan, Manohar; Verma, Mitusha; Harshe, Gayatri (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
The prevailing pandemic situation by SARS-CoV-2 infection is not only worrisome by the disease per se but also for the accompanying opportunistic infection are in the rise especially in diabetic patients. We presented a case series of post-covid rhino orbital cerebral mucormycosis infection in diabetic patients resulting in high morbidity. The need to present this was to emphasis on the timely surgical and medical intervention needed to reduce morbidity and mortality by the infection. The study highlighted the importance of surgical intervention in the deadly infection.